2019
DOI: 10.1111/cup.13454
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of lichenoid dermatitis immune‐related adverse event from immune checkpoint inhibitors reveals increased CD14+ and CD16+ monocytes driving an innate immune response

Abstract: Background Cancer patients receiving antibodies abrogating immune checkpoint pathways may develop a diverse array of immune‐related adverse events (irAEs), of which lichenoid dermatitis (LD) is the most common. The mechanism driving the emergence of these irAEs remain understudied, underscoring a critical need to determine the unique gene expression profiles and immune composition in LD—irAE. Methods LD—irAE (n = 3) and benign lichenoid keratosis (BLK) control (n = 3) were profiled with NanoString nCounter Pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…LD‐ICI are often mild irAEs that can be managed by topical steroids; however, on occasion, particularly with grade 3 irAEs, management includes systemic steroids and cessation of ICI therapy . Although the presence of CD8+ T‐cells at the periphery of the tumor has been associated with anti‐tumor response with ICI therapy, we and other have reported irAE from ICI therapy exhibit an infiltrate of CD4+ and CD8+ T‐cells, as well as monocytes . In this report, there was no clinical evidence of MF and both lesions are asymptomatic and continue to decrease in size.…”
Section: Discussionmentioning
confidence: 55%
“…LD‐ICI are often mild irAEs that can be managed by topical steroids; however, on occasion, particularly with grade 3 irAEs, management includes systemic steroids and cessation of ICI therapy . Although the presence of CD8+ T‐cells at the periphery of the tumor has been associated with anti‐tumor response with ICI therapy, we and other have reported irAE from ICI therapy exhibit an infiltrate of CD4+ and CD8+ T‐cells, as well as monocytes . In this report, there was no clinical evidence of MF and both lesions are asymptomatic and continue to decrease in size.…”
Section: Discussionmentioning
confidence: 55%
“…Innate immune cells can mediate irAE development likely both in cooperation with and independent of adaptive immune cells ( Lee et al, 2021 ). Studies have reported associations of irAEs with the recruitment of CD14 + CD16 + monocytes ( Curry et al, 2019 ), the presence of eosinophilia ( Kizawa et al, 2019 ), increased neutrophil/lymphocyte ratio (NLR) ( Drobni et al, 2020 ), as well as NK cell-mediated antibody-dependent cell-mediated cytotoxicity (ADCC) reactions ( Kelly et al, 2018 ). In addition to the innate immunity, seven genes related to the adaptive immune response also underwent alternative splicing and that were highly correlated with irAE risk ( Figure 4A ).…”
Section: Discussionmentioning
confidence: 99%
“…LD‐irAE is an inflammatory, immune‐mediated process and is the most common morphology biopsied (approximately 54%‐95% of all cutaneous irAE biopsies) in patients receiving ICI therapy 7,14 . While the immunopathogenesis of LD‐irAEs needs further investigation, contributing factors may include altered cutaneous microbiome and activation of the innate immune response along with involvement of the Toll‐like receptor (TLR)/CD14‐mediated pathway in susceptible patients 16 . The development of LD‐irAE from ICI therapy usually occurs at ~3 months after initiation of ICI therapy, but may range from a few weeks to several months 8 .…”
Section: Discussionmentioning
confidence: 99%